Materialklassifikation in optischen Inspektionssystemen mithilfe hyperspektraler Daten - Michelsburg, Matthias (Forschungsberichte aus der Industriellen Informationstechnik / Institut für Industrielle Informationstechnik (IIIT), Karlsruher Institut für Technologie, 2014)
In this work, different methods for material classification by hyperspectral images in the near infrared range are investigated. Specifically, the design of problem-adapted camera systems and the choice of optimal optical filters are discussed. In addition, a method for the fusion of multiple camera signals by spectral unmixing is presented.